Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To complete the table for the function [tex]\( f(x) = \sqrt{x-5} + 3 \)[/tex], we will evaluate the function at each of the given [tex]\( x \)[/tex] values. Here are the detailed steps for each calculation:
1. For [tex]\( x = 5 \)[/tex]:
[tex]\[ f(5) = \sqrt{5 - 5} + 3 = \sqrt{0} + 3 = 0 + 3 = 3 \][/tex]
Therefore, when [tex]\( x = 5 \)[/tex], [tex]\( y = 3 \)[/tex].
2. For [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = \sqrt{6 - 5} + 3 = \sqrt{1} + 3 = 1 + 3 = 4 \][/tex]
Therefore, when [tex]\( x = 6 \)[/tex], [tex]\( y = 4 \)[/tex].
3. For [tex]\( x = 9 \)[/tex]:
[tex]\[ f(9) = \sqrt{9 - 5} + 3 = \sqrt{4} + 3 = 2 + 3 = 5 \][/tex]
Therefore, when [tex]\( x = 9 \)[/tex], [tex]\( y = 5 \)[/tex].
4. For [tex]\( x = 14 \)[/tex]:
[tex]\[ f(14) = \sqrt{14 - 5} + 3 = \sqrt{9} + 3 = 3 + 3 = 6 \][/tex]
Therefore, when [tex]\( x = 14 \)[/tex], [tex]\( y = 6 \)[/tex].
After these calculations, the completed table is as follows:
[tex]\[ \begin{tabular}{c|c} x & y \\ \hline 5 & 3 \\ 6 & 4 \\ 9 & 5 \\ 14 & 6 \\ \end{tabular} \][/tex]
So, the values are:
- When [tex]\( x = 5 \)[/tex], [tex]\( y = 3 \)[/tex].
- When [tex]\( x = 6 \)[/tex], [tex]\( y = 4 \)[/tex].
- When [tex]\( x = 9 \)[/tex], [tex]\( y = 5 \)[/tex].
- When [tex]\( x = 14 \)[/tex], [tex]\( y = 6 \)[/tex].
1. For [tex]\( x = 5 \)[/tex]:
[tex]\[ f(5) = \sqrt{5 - 5} + 3 = \sqrt{0} + 3 = 0 + 3 = 3 \][/tex]
Therefore, when [tex]\( x = 5 \)[/tex], [tex]\( y = 3 \)[/tex].
2. For [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = \sqrt{6 - 5} + 3 = \sqrt{1} + 3 = 1 + 3 = 4 \][/tex]
Therefore, when [tex]\( x = 6 \)[/tex], [tex]\( y = 4 \)[/tex].
3. For [tex]\( x = 9 \)[/tex]:
[tex]\[ f(9) = \sqrt{9 - 5} + 3 = \sqrt{4} + 3 = 2 + 3 = 5 \][/tex]
Therefore, when [tex]\( x = 9 \)[/tex], [tex]\( y = 5 \)[/tex].
4. For [tex]\( x = 14 \)[/tex]:
[tex]\[ f(14) = \sqrt{14 - 5} + 3 = \sqrt{9} + 3 = 3 + 3 = 6 \][/tex]
Therefore, when [tex]\( x = 14 \)[/tex], [tex]\( y = 6 \)[/tex].
After these calculations, the completed table is as follows:
[tex]\[ \begin{tabular}{c|c} x & y \\ \hline 5 & 3 \\ 6 & 4 \\ 9 & 5 \\ 14 & 6 \\ \end{tabular} \][/tex]
So, the values are:
- When [tex]\( x = 5 \)[/tex], [tex]\( y = 3 \)[/tex].
- When [tex]\( x = 6 \)[/tex], [tex]\( y = 4 \)[/tex].
- When [tex]\( x = 9 \)[/tex], [tex]\( y = 5 \)[/tex].
- When [tex]\( x = 14 \)[/tex], [tex]\( y = 6 \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.